Pengaruh Budaya Organisasi dan Pengembangan Karir Terhadap Komitmen Organisasi : Dimediasi Oleh Kepuasan Kerja - Siti Khoirun Nisa; Diana Lestari; Agus Artono; Retno Purwani Setyaningrum (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This study aims to analyze the influence of organizational culture and career development on organizational commitment, with job satisfaction as a mediator. The study involved a sample of 91 employees from various divisions of the company. Data analysis was conducted using Smart PLS 3 software with a quantitative research method, and data collection was carried out through Google Forms. The results indicate that organizational culture and job satisfaction significantly positively influence organizational commitment. However, career development does not show a significant impact on organizational commitment at PT. Kimberly Clark Softex Karawang. The analyzed equation model includes the outer model, inner model, and hypothesis testing. These findings provide valuable insights for the company regarding factors that can strengthen the bond between employees and the organization. The study contributes to the development of human resource management at the company by highlighting key aspects that need attention to enhance organizational commitment. Practical implications of these findings can assist PT. Kimberly Clark Softex Karawang in optimizing organizational culture and job satisfaction as strategies to enhance employee commitment. Furthermore, recommendations for further evaluation of career development programs serve as a foundation for the company to design more effective initiatives to support employees' career growth in the future. In conclusion, it can be inferred that organizational culture and job satisfaction support organizational commitment.